The Role of School Leadership in Advancing Environmental Sustainability Through Curriculum, Community Engagement, and Strategic Initiatives - Zakariah, Zakariah; Ma'ruf, Fauzan; Wahyu, Asri Rezki (Educia Journal, 2024)
The objective of this qualitative study aims to identify and describe determinants of environmental sustainability in schools. By examining approaches adopted by the school leaders, teachers, and students in their experience and observations, the study discusses approaches to both formal and informal education for sustainable development with reference to the schools-in-the-round project. It also outlines the push factors we discussed earlier such as inadequate resources, management resistance, and the others as the challenges that few leaders experience in implementing sustainability in their institutions. Studies show that leadership plays an essential role in driving the culture of sustainability change by the champions, visionaries and facilitators. Main approaches to promote sustainability include including environmental topics into many areas of knowledge, making students participate in eco-clubs and sustainability fairs, and collaborating with NGOs and other organizations. However, they noted that emerging challenges that can prevent the proper implementation of the sustainability initiatives include inadequate funding and more so lack of enough time. Lack of staff and students support also slows down the process, the solution being communication and professional development training. The implications of this study for the field are that, unlike many previous research studies on the topic of education for sustainable development, this study seeks to illustrate the actual work of school leaders in the process and offer suggestions for addressing the issues discussed. Policymakers are only able to provide one-off support that helps fund short-term specific sustainability-based projects while the results demonstrate that schools require ongoing resources to achieve long-term goals.